ICTs to Remediate Writing Problems in Students with Special Learning Disabilities - Riga, Anna; Karabatzaki, Zoe; Geralexis, Ioannis (Eximia, 2023)
The purpose of this quantitative research is to investigate the opinions of Secondary Education teachers regarding the use of ICTs in strategies for remediating the writing problems of students with Special Learning Disabilities. Through this specific research work it is appropriate to highlight the advantages and disadvantages of the use of ICTs, the factors that prevent teachers from using them and if the learning objectives are achieved and the students are improved. The results showed that teachers have positive views on the use of ICTs in the teaching of students with Special Learning Difficulties and in strategies for the remediation of writing problems, while they consider their use easy. At the same time, despite their increased benefits, it is considered necessary to train teachers in the ICTs and enrich their programs. Finally, age, years of service and level of education are factors that differentiate teachers' opinions. The findings of the study are examined from the perspective of educational placement.